Innovation in Management of Pancasila and Citizenship Education - Karmin, Karmin; Saronto, Saronto (PPSDP International Journal of Education, 2025)
Innovation in learning program management is a key element in improving educational effectiveness. Innovation is defined as a new idea or practice that is accepted by an individual or group, while management is described as the art and science of organizing resources to achieve goals. Learning is understood as a process of interaction between teachers and students that results in behavioral changes. In the context of learning program management, the principal acts as an effective manager, ensuring that resources are managed optimally in accordance with the principles of effectiveness, efficiency, and economy. The definition of school-based management emphasizes greater autonomy for schools to innovate in resource management, with community participation as a determining factor for success. Management functions, including planning, organizing, implementing, and supervising, must be applied carefully to achieve the educational goals that have been set.